Probing solar storms with GRAPES-3 scintillator detectors. (February 2023) - Hariharan, B.; Chakraborty, M.; Dugad, S.R.; Gupta, S.K.; Hayashi, Y.; Jagadeesan, P.; Jain, A.; Kawakami, S.; Kojima, H.; Mahapatra, S.; Mohanty, P.K.; Muraki, Y.; et al.
Abstract: The GRAPES-3 muon telescope in Ooty, India detected a 2-h burst of cosmic ray muons (E μ ⩾ 1 GeV) on 22 June 2015 upon the arrival of a strong coronal mass ejection which triggered a G4 class geomagnetic storm. A detailed study of this event with the aid of Monte Carlo simulations suggests that the observed excess muons are due to a weakening of Earth's magnetic field caused by reconnection of the strong B z component of interplanetary magnetic field with that of Earth (Mohanty, 2016 ). This caused a lowering of the geomagnetic cutoff rigidity and led to the entering of excess threshold cosmic rays into the Earth's atmosphere. The event was also analyzed with the data recorded by the GRAPES-3 scintillator detector array. These detectors record cosmic ray shower particles above a few MeV energy in contrast to GeV threshold of the muon telescope, but they lack directional information. Here, we will present these results and compare them with the results from the muon telescope. We will discuss the relevance of these results to the space weather prediction.